Gender Empowerment, Supply-Chain Linkages and Foreign Direct Investment : Evidence on Bangladesh - Fernandes, Ana M.; Kee, Hiau Looi (World Bank, Washington, DC, 2020)
This paper studies foreign direct investment spillovers on the gender-related labor market practices of domestic firms, based on a unique firm-to-firm data set of Bangladesh's textiles and garment sectors. The paper looks at the female employment of domestic firms that are directly and indirectly related to foreign direct investment firms through supply chain linkages. These domestic firms are either the local suppliers or customers of foreign direct investment firms, or they share local suppliers and customers with foreign direct investment firms. The estimates show that domestic firms related to foreign direct investment firms have significantly more female administrative workers, but not necessarily female non-administrative workers, due to the former participating in more firm-to-firm interactions.